HUBUNGAN DUKUNGAN KELUARGA DENGAN KEBERHASILAN PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA DI WILAYAH KERJA PUSKESMAS BRINGIN KABUPATEN SEMARANG - Vera Mei Kartika; Fitria Primi Astuti; Isfaizah (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2017)
Mother's Milk (ASI) is the best food for babies, because of its nutrient content is very special and perfect and in accordance with the needs of infant growth. The success rate of exclusive breastfeeding lowest in Semarang Regency namely Puskesmas Bringin which do not meet the national target of 80% this is due to lack of support provided by the family. Mothers breastfeed their babies is determined by the support of family, husbands, health workers, community, and work environment. The purpose of this study was to determine the relationship between family support with the success of exclusive breastfeeding in mothers working in Puskesmas Bringin Semarang regency.This research method is descriptive correlational research. The population of as many as 45 respondents. Sampling with a total sampling. The technique of collecting data using questionnaires about family support and breastfeeding. Analyzed using univariate and bivariate analysis using Fisher exact test results.The results showed that family support in the success of exclusive breastfeeding in mothers working in Puskesmas Bringin Semarang regency mostly less as many as 24 people (53.3%). Most mothers work in Puskesmas Bringin Semarang district does not give exclusive breastfeeding as many as 35 people (77.8%). There is a relationship between family support with the success of exclusive breastfeeding in mothers working in Puskesmas Bringin Semarang district with a value of 0.029. Suggestions to the respondent can form groups of working mothers who breastfeed so that they can share their knowledge and experience of the successful exclusive breastfeeding.